Characterization of carbon nanotube reinforced aluminium nano-composite using field emission scanning electron microscope - Abdullahi, Umma; Maleque, Md. Abdul; Ali, Mohammad Yeakub (Deer Hill Publications, 2018)
Carbon nanotubes (CNT) is a promising fibrous materials for development of nanocomposite especially aluminium (Al) matrix nanocomposites as CNT exhibited extraordinary mechanical properties and high aspect ratios. The dispersion is the main factor for a quality CNT-Al nanocomposite that affects the uniformity in mixture leading to the enhanced mechanical and wear behaviour. The present study emphasizes on the characterization of carbon nanotube dispersion by means of field emission scanning electron microscope after synthetization of new nanocomposite. The mixing of the reinforcement and matrix powders was performed in ball mill for 2 hours at 250 rpm. The result shows the homogeneous distribution was observed from the experiment. The morphological characterization under FESEM provides insight features of CNT-Al nano-composite with the ball milling parameter on the sintering.